Individualism vs. Collectivism - How inherited cultural values affect the labor market outcomes of second generation immigrants in the US - Lisa Sofie Höckel (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
The cultural diversity induced by migration has been proven beneficial to host countries economies and the labor market performance of second generation immigrants is a crucial determinant of integration. Labor market returns to different cultural traits, however, have been rarely studied within the economic literature. Therefore, this study provides insights on the link between the level of collectivsm at the country of ancestry and labor market outcome of second generation immigrants in the US. Using 1994 - 2014 census data, we analyze the impact of inherited cultural differences on the economic outcome of more than 21,000 male homogamous second generation immigrants. We use the disease environment of the country of ancestry as a measurement for collectivism and find that higher scores of collectivism are associated with higher income earned in the US. We demonstrate that labor force participation is one of the main determinants of the positive impact of collectivism on earnings. Further, we are the first to investigate occupational choice as a channel through which inherited cultural values affect individuals' behavior in the labor market. We show that second generation immigrants with an individualistic ancestry are more likely to self-select into jobs which require individualistic abilities such as independence. Second generation collectivists prefer jobs which demand collectivistic traits such as sensibility towards others. We argue that second generation immigrants with a collectivistic ancestry take different jobs than individualists due to inherent comparative advantages in performing particular productive tasks. Overall they perform better than their individualistic counterparts. Our findings are robust to the use of other measures of collectivism and different data compositions.
Keywords: A13; F22; J24; 330